Base-Catalyzed Tandem Cyclization: Diastereoselective Access to the 3,4-Dihydroisoquinolin-2(1H)-one Core - Shirsat, Prashishkumar K.; Khomane, Navnath B.; Meshram, Sneha H.; Sridhar, Balasubramanian; Meshram, Harshadas M.; Kumbhare, Ravindra M. (Synthesis, 2019)
A novel, one-pot reaction for the synthesis of 3,4-dihydroisoquinolin-2(1H)-one derivatives is developed via a base-mediated three-component reaction of ninhydrin, aniline and acetylenic esters. This diastereoselective reaction takes place in methanol at 70 °C under transition-metal-free conditions, and direct construction of the C–N and C–C bonds is readily achieved via tandem cyclization. These cyclic frameworks are resourceful small molecular keys to many natural products.
Keywords: ninhydrin; anilines; 3,4-dihydroisoquinolin-2(1H)-ones; methanolysis; tandem cyclization